FORMATION AND DEVELOPMENT OF THE MOBILE TV MARKET IN THE 20TH CENTURY - I. Levitina (Вестник университета)
The history and development of the mobile television market in the 20-th century have been considered. The history of the mobile television market includes scientific research, responding to market needs and business risk. This allows you to solve a whole range of tasks: from space exploration to the launch of a commercially profitable product with unique consumer qualities. Modern mobile television is a rapidly developing branch of the national economy. The objective of this research is to fill the lack of coverage in the domestic economic-scientific literature of the processes of formation and development of the world market of mobile television (this paper is part of the special complex materials for higher education).